MEDIATION EFFECT OF WORK ENVIRONMENT ON ORGANIZATIONAL CULTURE IN IMPROVING EMPLOYEE PERFORMANCE - Tehubijuluw Zacharias (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to analyze the influence of work environment mediation on organizational culture in improving the performance of employees of BKPSDM South Buru Regency. This study uses a descriptive-quantitative approach with a causal correlation type. The research was conducted at BKPSDM South Buru Regency. The population used in this study were all employees at the BKPSDM South Buru Regency, consisting of 64 people. The method of determining the sample is full sampling. Data were analyzed using path analysis. The results of the study concluded that (1) organizational culture has a positive and significant effect on employee performance; (2) organizational culture has a positive and significant effect on the work environment of employees ; (3) the work environment has a positive and significant effect on employee performance ; (4) organizational culture has a positive and significant effect on performance through the work environment of employees.